Учетно–аналитические аспекты системы управления затратами предприятий отрасли птицеводства - Майданевич, П.Н. (Культура народов Причерноморья, 2014)
В статье рассмотрены теоретические и методические аспекты системы управления
деятельностью современных субъектов предпринимательской деятельности, показана возрастающая
роль и значение затрат как объектов управления. Исследованы особенности системы управления
затратами птицеводческих предприятий, обусловленные внедрением инновационных технологий,
избыточным предложением и усилением внутриотраслевой конкуренции. Отражена роль учета и
анализа как элементов системы управления затратами, проведен факторный анализ суммы и уровня
затрат предприятий отрасли птицеводства АР Крым, предложены направления совершенствования
политики управления затратами в части построения системы их рационального учета. Раскрыты
возможности совместного применения нормативного метода учета затрат и системы «директ–
костинг» на предприятиях, специализирующихся на производстве яиц и мяса птицы. У статті розглянуті теоретичні та методичні аспекти системи управління діяльністю
сучасних суб'єктів підприємницької діяльності, показані зростаюча роль і значення витрат як об'єктів
управління. Досліджені особливості системи управління витратами птахівницьких підприємств,
обумовлені впровадженням інноваційних технологій, надлишковою пропозицією та посиленням
внутрішньогалузевої конкуренції. Відображено роль обліку та аналізу як елементів системи управління
витратами, проведено факторний аналіз суми та рівня витрат підприємств галузі птахівництва АР
Крим, запропоновані напрямки удосконалення політики управління витратами в частині побудови
системи їх раціонального обліку. Розкриті можливості спільного застосування нормативного методу
обліку витрат і системи «директ–костінг» на підприємствах, що спеціалізуються на виробництві яєць і
м'яса птахів. In the article the theoretical and methodical aspects of control system are considered activity of
modern performers of entrepreneurial activities, an increasing role and value of expenses are shown as
management objects. Determination of concept «control system by expenses» is given, the tasks of control system
are exposed by expenses, the role of backlogs of cost cutout is exposed on a production and realization of
products of enterprises as a source of increase of their profitability and profitability. The features of control
system are investigational the expenses of poultry farming enterprises, conditioned by introduction of innovative
technologies, surplus suggestion and strengthening of competition. The role of account and analysis is reflected
as elements of control system by expenses, the estimation of level of expenses is given in comparison with the
dynamics of profit yield (acuests) from realization of products of the poultry farming, the factor analysis of sum
and level of expenses of enterprises of industry of the poultry farming is conducted ARE Crimea. Directions of
perfection of politics offer.